Multi-instrument study of footprints of magnetopause reconnection in the summer ionosphere - S. E. Pryse; A. M. Smith; I. K. Walker; L. Kersley (Annales Geophysicae, 2000)
Results are presented from a multi-instrument investigation of the signatures of equatorial reconnection in the summer, sunlit ionosphere. Well-established ion dispersion signatures measured during three DMSP satellite passes were used to identify footprints in ionospheric observations made by radio tomography, and both the EISCAT ESR and mainland radars. Under the prevalent conditions of southward IMF with the Bz component increasing in magnitude, the reconnection footprint was seen to move equatorward through the ESR field-of-view. The most striking signature was in the electron temperatures of the F2 region measured by the EISCAT mainland radar that revealed significantly enhanced temperatures with a steep equatorward edge, in general agreement with the leading edge of the ion dispersion. It is suggested that this sharp transition in the electron temperature may be an indicator of the boundary, mapping from the reconnection site, between closed geomagnetic field lines and those opened along which magnetosheath ions precipitate. Key words: Ionosphere (ionosphere-magnetosphere interactions; particle precipitation; plasma temperature and density)